Effects of carbon dioxide purities on mitotic index in lymphocyte culture and metaphase chromosome quality - Sofiati Purnami; Indri Permata Wibisari; Viria Agesti Suvifan; Siti Nurhayati; Dwi Ramadhani (Nusantara Bioscience, 2021)
Abstract. Purnami S, Wibisari IP, Suvifan VA, Nurhayati S, Ramadhani D. 2021. Effects of carbon dioxide purities on mitotic index in lymphocyte culture and metaphase chromosome quality. Nusantara Bioscience 13: 171-176. The metaphase chromosome spread quality is necessary for a faster individual dose prediction following radiological accidents using dicentric chromosome assay. It is well known that the low-quality metaphase chromosome spreads can lead to false positives of dicentric chromosome identification. Thus, evaluating the main variable that influences the preparation of high-quality metaphase chromosome spread is important. Until now, no studies have assessed the effects of CO2 purities on metaphase chromosome spread quality. This study aimed to evaluate the effects of carbon dioxide (CO2) purities on lymphocyte proliferation and the quality of metaphase chromosome spreads to improve the chromosome aberration assay for cytogenetic biodosimetry purposes. Whole blood samples from three subjects were cultured and incubated for 48 hours with two different grades of CO2 (high purity and food grades) and without CO2. Each subject's mitotic index (MI) was assessed, and the quality of metaphase chromosome spreads was evaluated by comparing the lengths of chromosomes 1, 2, and 21. Statistical analysis revealed that the difference between manual and automatic MI under three conditions of CO2 purity was not statistically significant (p = 0.162; p = 0.901). Comparative analysis of the lengths of chromosomes 1, 2, and 21 from 145 metaphases also showed a difference that was not statistically significant (p = 0.745; p = 0.915; p = 0.399). Our findings suggest that CO2 purities do not impair lymphocyte proliferation or metaphase quality. Further investigation should include other technical improvements, such as drop-slide optimization.